Effect of Polysulfone Content on Forward Osmosis Membrane Performance. - ustafa, Haikal M; Onn, Munirah; Zainuddin, Aznilind; Mariam bt Mohammad Iliyas, Siti; Pei Sean, Goh; Fauzi Ismail, Ahmad (International Journal of Engineering and Technology, 2018)
Desalination is the process to separate salt content from saline water. This study observes the effect of different polysulfone (psf) content on forward osmosis (FO) membrane towards its water flux and salt rejection performance. The loading percentages of psf used in the membrane are 15%, 15.5% and 16%. Theoretically, the higher the psf content, the lower the water flux passes through membrane. The membranes were prepared using interfacial polymerization technique and tested through reverse osmosis (RO) process and FO setup.Â From the reverse osmosis (RO) experiment, the results showed that the salt rejection of 15% psf, 15.5% psf, 16% psf, are 92.94%, 93.71%, 95.98% respectively. In the FO experiment, the water flux results recorded for 15% psf, 15.5% psf, 16% psf, content are 1.21 L/m2h, 0.43 L/m2h, 0.21 L/m2h, respectively. Based on these two parameters, it would seem that by increasing the psf content the salt rejection value had increased but the water flux had decreased accordingly. These trends may due to when the psf content was increased; the support layer became denser and less porous which would lead to a higher solute rejection and lower water flux through the membrane. In conclusion, increasing of psf content will give forward osmosis membrane with higher salt rejection but lower water flux. Â Â